К проблеме эволюции надпочечных желез и их нервных структур у позвоночных - Агарков, Г.Б. (Вестник зоологии, 1967)
The formation of the suprarenal glands and their nervous apparatus in philogeny are inadequately discussed in the present literature. With the aim of investigating the morphology and innervation of these glands, the author studied them in representatives of all classes of vertebrates. The transformation of interrenal and chromaffin bodies of teleost fish into the complex paired suprarenals of the higher vertebrates is traced.
The results show that in the process of evolution complication and specialization occur in the nervous apparatus of the suprarenals and their nerve connections with the central nervous system, which are of importance in regulating and effecting the functions of the glands.